Marketing Strategy for Savings Fund Collection Products at PT. BPRS Lantabur Tebuireng Gresik Branch - Sukartini, Lisa; Sukaris, Sukaris (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to identify the marketing strategies used by BPRS Lantabur Tebuireng, Gresik Branch in promoting savings fund collection products, and to understand the role of these strategies in the marketing process of these products. This research uses a qualitative methodology that applies a descriptive approach, where the research findings are presented in depth in narrative form to facilitate understanding. For data collection, researchers utilize various techniques, including observation, documentation, and interviews. The informants of this study consisted of funding officer staff of BPRS Lantabur Tebuireng, Gresik Branch and savings customers at the branch. The problem experienced by BPRS Lantabur Tebuireng, Gresik Branch is what marketing strategy is used by BPRS Lantabur Tebuireng, Gresik Branch in marketing Savings Fund Collection Products. The first finding shows the ball pick-up strategy used by BPRS Lantabur Tebuireng, Gresik Branch. The second finding shows what obstacles occur during the implementation of the ball pick-up strategy. The third finding shows which Savings products are most in demand by customers. According to the results of the discussion, the outreach strategy has proven successful in marketing savings products.